Towards enhancing the health standards of elderly: role of ambient sensors and user perspective. (29th April 2022) - Patel, Ashish; Shah, Jigarkumar
Smart home and smart health are two significant components of ambient assisted living systems (AALs). The AAL systems uses wireless sensor network as a backbone to develop smart environments. The prime objective of AAL is to extend the time in which older adults stay independently in their preferred environment. This objective makes AALs more sensitive towards a person's day-to-day life. Researchers from the sphere, proposed a large number of solutions, but very few precisely addressed the user's perspective. A considerable percentage of the elderly population may not be interested only in the ease of living. However, they may be more inclined towards health-related services. This situation needs some substantial development in the sphere of intelligent assistive systems. This proposal aims to address the answer to this problem through subjective evaluation of AAL system. In-depth analysis is performed on the user's viewpoint using the questionnaires, revealing potential AAL users' unique requirements. The work presented here incorporates the user's perspective in designing a smart healthcare system. The proposed approach is evaluated using various datasets utilising conventional sensor data, sensor data with visual input and sensor data with human emotion. Different deep learning algorithms are applied to predict personal health.